Exploration of barriers and possible solutions for nonutilization of facility-based integrated counseling and testing center using the delphi technique - Reenaa Mohan; Pravin Surendran; M Rajalakshmi; Kalaiselvan Ganapathy (Wolters Kluwer Medknow Publications, 2023)
Background: A major group of the population, especially antenatal checkup (ANC) mothers and their spouses, people admitted for surgery, and people attending STI clinics, are reluctant to pretest counseling. Objectives: This study has been taken up to explore the barriers and possible solutions to improve the utilization of Facility based integrated counseling and testing center (F-ICTC) counseling services. Materials and Methods: Phase 1: In-depth interview and ranking with stakeholders from the F-ICTC center (n = 13) were conducted to identify the barriers to utilization of F-ICTC and solution for the same. Phase 2: A Delphi panel with experts (n = 17) was invited through mail to find out the potential solution to improve the utilization of F-ICTC counseling services. Results: Possible barriers from the stakeholders' perspectives were fear of the disease, violate the privacy, unacceptance, gender bias, fear of social stigma and discrimination, and neglect attached to the disease. At third round of Delphi experts had arrived at a consensus regarding of following possible potential solutions: 1.Those who refuse pretest counseling they should be asked to answer a set of questions(which are usually told during counseling), only those questions not answered correctly by them can be corrected, 2.conducive hospital environment, 3.zero discrimination policy, 4. group counseling for ANC mothers and patients in waiting area of the hospital,5. phone counseling for unwilling patients and relocation of testing center and health education camping. Conclusion: Context-specific proactive evidence-based intervention will help in improving the proper utilization of the F-ICTC center.